Artisanal upcycling and differents biotypes: conception, development and production of conceptual fashion products (ModaPalavra e-periódico, 2023)
This article aims to present the human body, in all its planes – coronal, sagittal and transversal – and its importance for the conception, development and production of artisanal upcycling in conceptual fashion products. This is an applied, qualitative and descriptive research outlined by a bibliographical research – from authors linked to semiotic theorization of the body and Swedish authors involved in creative methods – and experimental – with laboratory research. Accompanying pro-sustainability studies, the upcycling technique ethically seeks to improve the creation of fashion products that can be reconfigured and arranged again in the circular economy of fashion, and body studies can contribute to body diversity be linked in the aesthetic and authorial conception of these products that are reintroduced by the creative act of seeing and doing.
Keywords: upcycling; creative process; body